Pendampingan Penyusunan Anggaran Produksi Pada UMKM Mitra Markisa Toraja Kecamatan Rantetayo Kabupaten Tana Toraja - Srisetyawanie Bandaso; Althon K. Pongtuluran; Agustinus Mantong; Jens Batara Marewa; Randi Tangdialla; Ade Lisa Matasik (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Mitra Toraja Markisa is a family business in Rantetayo sub-district which produces passion fruit into a drink that is rich in benefits. Production at Mitra Markisa Toraja has several obstacles that often affect the production process, including the limited passion fruit as the raw material in making the product, resulting in the expected production target sometimes not being achieved. This limitation of raw materials is caused by several things such as the failure of the passion fruit harvest due to plant pests or other things, the type of passion fruit needed sometimes experiences a decrease in stock because it is much sought after and other problems. In recording its production reports/budgets, Mitra Markisa Toraja still records manually in the ledger, which is recorded for one period/year. The products produced by Mitra Markisa Toraja have been distributed throughout Tana Toraja and North Toraja and have even been shipped outside Toraja. The purpose of the research to be achieved is to determine the results of the production budget analysis at the Mitra Toraja Markisa Industry.